An empirical assessment of ICT diffusion in Africa and OECD. (18th December 2009) - Bagchi, Kallol K.; Udo, Godwin J.
In the present study we examine those factors that affect the diffusion of Information and Communications Technology (ICT) in Africa and the Organisation for Economic Cooperation and Development (OECD) over a period of over 21 years. A dynamic comparison highlights the major differences in ICT diffusion between developing and developed nations. A large set of data from the World Bank was used; a pooled regression analysis shows that economic development, education/training, and infrastructures play a significant role in ICT diffusion. It was further observed that the effects of some factors could be similar whereas effects for some other factors could be different for developed and developing nations. The results further indicated that mobile phone and mainline telephone diffusions are substitutive in OECD nations but complementary in African nations.